Valoración del grado de satisfacción y confort de los pacientes con prótesis total implanto asistida“Monoblock”. - Morales Cobos, Jorge David (2017)
This investigation was carried out in order to determine the degree of satisfaction and comfort of patients receiving over denture treatments, to improve their personal and nutritional aspect, the most appropriate procedure for people with total edentulous or they have lost the alveolar edge for different circumstances pointing among the main causes for their dental extraction as (caries or fractures of the dental piece). The investigation was carried out in the months of November and December of the current year; in the cities of: Quito, Guayaquil, Ambato, among other cities, with people over 40 years of age, who underwent this type of dental rehabilitation. This investigation has as main objective to evaluate the degree of satisfaction and comfort of the patients with total prosthesis, assisted implant. The results indicated that 100% of the patients surveyed were satisfied with the treatment, had comfort with their prosthesis, can chew food normally, pronounce words well, and even recommend treatment to other people. In conclusion, the present investigation shows a high degree of success in the treatment and efficacy when normally fulfilling the different functions in the oral cavity, such as: phonetics, chewing, and dental aesthetics, where I can also observe total satisfaction and comfort of the patient with the treatment performed, being a safe method for the placement of the total prosthesis with immediate loading, and recommended by patients who have undergone this treatment.